2003
DOI: 10.1002/ana.10606
|View full text |Cite
|
Sign up to set email alerts
|

Elevated osteopontin levels in active relapsing‐remitting multiple sclerosis

Abstract: In the search for proteins that might play a role in the pathogenesis of multiple sclerosis (MS), osteopontin (OPN) has been identified as the most prominent cytokine-encoding gene expressed within MS lesions. Here, we report significantly increased OPN protein levels in plasma of relapsing-remitting MS patients. In contrast, OPN protein levels in primary progressive and secondary progressive MS patients were similar to healthy control levels. Interestingly, active relapsing-remitting patients had higher OPN p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 19 publications
2
86
1
3
Order By: Relevance
“…37 Moreover, several reports detected high serum levels of osteopontin, a cytokine capable to inhibit AICD, in MS patients and we found that this is partly associated with variants of the osteopontin gene. [38][39][40][41] In conclusion, this work suggests that PRF1 variations may be a predisposing factor for MS by affecting either the antiviral response or the immune response switching off. Defects of both of these functions may favor development of autoimmunity by prolonging the immune response and increasing the risk of crossreactions between viral and self-antigens.…”
Section: Discussionmentioning
confidence: 69%
“…37 Moreover, several reports detected high serum levels of osteopontin, a cytokine capable to inhibit AICD, in MS patients and we found that this is partly associated with variants of the osteopontin gene. [38][39][40][41] In conclusion, this work suggests that PRF1 variations may be a predisposing factor for MS by affecting either the antiviral response or the immune response switching off. Defects of both of these functions may favor development of autoimmunity by prolonging the immune response and increasing the risk of crossreactions between viral and self-antigens.…”
Section: Discussionmentioning
confidence: 69%
“…The plaques found in human multiple sclerosis patients have a 5-fold increase in OPN transcripts (Chabas et al, 2001). Significantly increased OPN protein levels were found in the plasma of relapsing-remitting MS patients whereas the OPN protein levels in primary progressive and secondary progressive MS patients were similar to healthy control levels (Vogt et al, 2003).…”
Section: Autoimmunitymentioning
confidence: 86%
“…Increased levels of OPN transcripts were reported in both the brain tissue of MS patients and the spinal cords of an EAE rat model (Chabas et al, 2001). In contrast, in autoimmune myocarditis it appears that neither OPN nor CD44 play any role in the development of the disease (Vogt et al, 2003).…”
Section: Autoimmunitymentioning
confidence: 99%
“…Further characterization by the same investigators revealed that OPN plays a critical role in the induction and disease process of EAE, an animal model for MS, when they compared WT with OPN gene knockout mice [14]. More recently, studies have confirmed that serum levels of OPN appear elevated in patients with MS as compared with controls [15][16][17], raising the possibility that the phenomenon may be attributable to inflammatory processes in MS. However, although the properties of OPN as a pro-inflammatory cytokine are known, the exact mechanism underlying the role of OPN in CNS inflammation in MS remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%